Selective BCL-XL inhibition promotes apoptosis in combination with MLN8237 in medulloblastoma and pediatric glioblastoma cells. Issue 2 (20th July 2017) - Levesley, Jane; Steele, Lynette; Brüning-Richardson, Anke; Davison, Adam; Zhou, Jia; Ding, Chunyong; Lawler, Sean; Short, Susan C
Abstract: Background: CNS tumors, including medulloblastoma and pediatric glioblastoma (pGBM) account for the majority of solid pediatric malignancies. There remains an unmet need to identify novel treatment approaches in poor prognosis and relapsed pediatric brain tumors, where therapeutic options are limited. Small-molecule B-cell lymphoma 2 (BCL-2) family inhibitors may enhance tumor cell killing when combined with conventional and targeted chemotherapeutic agents. We investigated the effect of disrupting BCL-2 and B cell lymphoma-extra large (BCL-XL ) protein function using ABT-263, ABT-199 and WEHI-539 in medulloblastoma and pGBM cells following treatment with MLN8237, an Aurora kinase inhibitor under investigation as a novel agent for the treatment of malignant brain tumors. Methods: Tumor cell growth and viability were determined by MTT/WST-1 assays and flow cytometry. Effects on cell phenotype, cell cycle progression, and ploidy were determined by live cell imaging and DNA content analysis. Apoptosis was determined by annexin V/propidium iodide staining and time-lapse microscopy and confirmed by measuring caspase-3/7 activity and western blotting and by short interfering RNA (siRNA) knockdown of BCL-2 associated X protein/BCL-2 antagonist killer (BAX/BAK). Results: ABT-263, in combination with MLN8237, reduced mitotic slippage and polyploidy and promoted the elimination of mitotically defective cells via a BAX/BAK-dependent, caspase-mediated apoptotic pathway. The BCL-XL antagonist, WEHI-539, significantly augmented tumor cell killing when used in combination with MLN8237, as well as sensitized resistant brain tumor cells to a novel BAX activator, SMBA1. In addition, siRNA-mediated knockdown of BCL-XL sensitized pGBM and medulloblastoma cells to MLN8237 and mimicked the effect of combination drug treatment. Conclusion: Selective small-molecule inhibitors of BCL-XL may enhance the efficacy of MLN8237 and other targeted chemotherapeutic agents.